Kualitas Pelayanan Izin Mendirikan Bangunan (IMB) Di Kabupaten Sumedang (Studi Kasus Di Kecamatan Cimalaka) - Hagia Harsanti (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2018)
This study aims to determine the Public Perception of Building Construction Permit (IMB) in the Cimalaka District, Sumedang Regency. This research is a descriptive research with qualitative method. The theory used to analyzing data is Service Quality Theory (Servqual) from Zeithaml, Parasuraman and Berry. It has five dimensions; those dimensions are physical proof, reliability, responsiveness, assurance and empathy.The result of this study indicates that public perceptions of the quality of IMB services in Cimalaka District in Sumedang Regency is good enough. It could be seen from the physical dimension, reliability dimension, responsiveness dimension, assurance dimension, and empathy. The things that need to be improved by the Cimalaka District in providing IMB services are improvement of facilities and equipment used, increasing accuracy and competency of officers, certainty of time in completing services, enhancing credibility and security, as well as improving the ability in effective communication between officers and the community.